A typology of strategies that recognize, reward, and incentivize blood donation. Issue 10 (4th August 2022) - Chell, Kathleen; Masser, Barbara; Davison, Tanya E.; Ferguson, Eamonn
Abstract: Background: Blood collection agencies (BCAs) worldwide are continuously looking to improve recognition, reward, and incentive (RRI) policies to optimize the recruitment and retention of blood donors. However, given the inconsistent categorization and variety of strategies available, there is a need for a theoretically informed and empirically supported framework to guide RRI research and policy development. Study Design and Methods: Survey data from 1028 voluntary nonremunerated whole blood and plasma donors in Australia was used to validate a theorized RRI typology based on distinctions between the level of congruency with the act of donating blood (congruent vs. incongruent), visibility of acknowledgment (public vs. private), benefits provided (self vs. other), and likely reinforcement schedule (fixed vs. variable). Results: A six‐factor solution met all statistical criteria and was most consistent with a priori theoretical underpinnings. The factors were labeled (i) deal promotion, (ii) loyalty program, (iii) BCA token, (iv) health check, (v) charity donation, and (vi) travel compensation. Discussion: This typology provides researchers with a standardized theoretical and conceptual framework to organize and synthesize findings from the existing literature and help BCAs develop RRI policies that are likely to be successful. We present a future research agenda across and within the RRI strategies.